La tradition ecclésiastique gallicane à l’épreuve de la Révolution - François Hou (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
Deeply marked by the heritage of Bossuet and Fleury, Gallican Catholicism developed under the Ancien Régime a conception of Tradition strongly imbued with primitivism which was based both on the conservation of the practices of Antiquity and on the apostolic succession of bishops. By upsetting the exercise of spiritual jurisdiction, the Civil Constitution of the Clergy of July 12, 1790 led to two antagonistic reinterpretations of Tradition which made the French Revolution appear as a moment of discontinuity and innovative revivals of Gallican heritage.